A stitch in time: narrative review of interventions to reduce preterm births in Malawi. Issue 3 (23rd December 2019) - Batura, Rekha; Colbourn, Tim
Abstract: Background: The rising rate of preterm births (PTBs) is a global concern, and Malawi has a high rate of PTBs (10.5%). The resulting neonatal and under-5 mortality, morbidity and lifelong disability represent a significant loss of human potential affecting individuals, families and society as a whole. This study aims to review the literature to determine the risk factors for PTB in Malawi and to identify effective interventions to prevent PTBs. Methods: A literature search yielded 22 studies that were categorized according to risk factors implicated for PTBs and health interventions to reduce the risks. Results: The study has shown that maternal pregnancy factors, infections, nutrition, anaemia and young maternal age are the main causes and risk factors of PTBs in Malawi. The literature revealed no evidence of community-based interventions for reducing the rates of PTBs in Malawi. Conclusions: Any successful effort to reduce the rate of PTBs will require a multisector, multilevel strategy targeted at the community, homes and individuals as a package to improve the education, nutrition and reproductive health of girls and women as well as focus on improving the delivery of antenatal services in the community.